Review of the existing maximum residue levels for novaluron according to Article 12 of Regulation (EC) No 396/2005 - European Food Safety Authority (EFSA); Giulia Bellisai; Giovanni Bernasconi; Alba Brancato; Luis Carrasco Cabrera; Lucien Ferreira; German Giner; Luna Greco; Samira Jarrah; Renata Leuschner; Jose Oriol Magrans; Ileana Miron; et al. (EFSA Journal, 2022)
Abstract According to Article 12 of Regulation (EC) No 396/2005, EFSA has reviewed the maximum residue levels (MRLs) currently established at European level for the pesticide active substance. Although this active substance is not authorised within the European Union, MRLs were established by the Codex Alimentarius Commission (codex maximum residue limits; CXLs) and import tolerances were reported by Member States and the UK (including the supporting residues data). Considering that no toxicological reference values are currently established in Europe for novaluron because the peer review for the approval was terminated before an EFSA conclusion was issued, the toxicological profile of novaluron was also assessed, in order to be able to perform the consumer risk assessment in the framework of the art 12 MRL review. Based on the assessment of the available data, toxicological reference values were derived, and a consumer risk assessment was carried out for the existing CXLs and import tolerances. All CXLs and import tolerances were found to be supported by inadequate data and a possible chronic risk to consumers was identified. Hence, further consideration by risk managers is needed.